DESENVOLVIMENTO DO HÍBRIDO DE EUCALIPTO GRANCAM SUBMETIDO À IRRIGAÇÃO NOS PRIMEIROS 4 ANOS DE IMPLANTAÇÃO, EM AQUIDAUANA-MS - Xavier, Thiago; Lopes, Adriano; Do Val, Carla; Brito, Kelvin; Domingos, Eli; De Barros, Samara (ANAIS DO ENIC, 2018)
-